Explainer Video Creation as a Medium for Academic English Development Among Screenagers - Wulandari, Cok Istri Agung Sri; Permatasari, Ni Putu Intan; Suantika, I Kadek Dony; Ningrum, Ida Ayu Fortuna (Journal of English Language and Education, 2026)
In the digital era, screenagers learners immersed in technology prefer interactive and visually engaging learning approaches. This study examines the use of explainer video creation as a medium for developing academic English skills, particularly writing, speaking, and critical thinking. Using a descriptive qualitative design, the study involved 78 second-semester university students enrolled in an Academic English course who completed an explainer video project. Data were collected through video content analysis and open-ended student perception surveys. The study aimed to: (1) investigate how explainer video creation supports academic English development and (2) explore students’ perceptions and challenges during the video creation process. The findings indicate improvement in academic vocabulary use, coherence, pronunciation, and learner engagement. Students reported increased motivation and confidence, as the task required planning, scripting, rehearsing, and revising language output. However, challenges related to technical issues, time management, and collaboration were also identified. Overall, the study highlights the pedagogical potential of student-generated explainer videos in Academic English instruction and suggests that clear rubrics, technical guidance, and structured timelines are essential for maximizing learning outcomes.